The roles of emotional intelligence, interpersonal skill, and transformational leadership on improving construction safety performance (Construction Economics and Building, 2013)
Due to the characteristics of the constructionindustry, human skills are essential for working with and through others inmanaging safety. Research has shown that emotional intelligence, interpersonalskill, and transformational leadership are human skill components that generatesuperior performance in today’s workplace. The aim of this research is toinvestigate the influence of project management personnel’s human skills on theimplementation of safety management tasks and development of safety climate inconstruction projects. The structural equation modelling (SEM) method wasapplied to analyse the quantitative data collected and establishinterrelationship among the research variables. The results indicate thatemotional intelligence is a key factor for developing interpersonal skill andtransformational leadership, and for implementing safety management tasks whichleads to the development of safety climate. This research also found thatinterpersonal skill is needed for becoming transformational leaders whocontribute to the development of safety climate.